Formulation and efficacy testing of bio-organic fertilizer produced through solid-state fermentation of agro-waste by Burkholderia cenocepacia. (March 2022) - Bibi, Fatima; Ilyas, Noshin; Arshad, Muhammad; Khalid, Azeem; Saeed, Maimoona; Ansar, Sabah; Batley, Jacqueline
Abstract: Bio-organic fertilizers (BIOs), prepared from inoculating plant growth-promoting rhizobacteria (PGPR) into agro-industrial wastes, are gaining more attention due to their tremendous positive effects on soil health. This study was conducted to prepare and evaluate the effect of bio-organic fertilizers on maize. Plant growth-promoting rhizobacteria were isolated from rhizospheric soil of farmer's field near Islamabad, Pakistan and were screened for plant growth promotion characters and one strain Burkholderia cenocepacia was selected based on PGPR's characteristics. In-vitro characterization, the whole genome sequence analysis, RAST and antiSMASH analysis were performed. The number of coding sequences was 7157 with the number of subsystems 382. The GC contents included 66.96%. The sequence was submitted to NCBI with BioProject submission number PRJNA730996. Inoculum of selected bacterial strain Burkholderia cenocepacia was used for carrying solid-state fermentation of organic wastes. Four different agro-industrial wastes with a good amount of crude protein were selected: black gram husks (BGH) (15–22% Crude protein CP), rice bran (RB) (10–15% CP), peanut shell (PS) (6–7% CP), and dry leaves (DL) (as conventional fertilizers for comparison) were collected, dried, ground and sieved. Different parameters like pH, moisture content, particle size, temperature etc. were optimized. Inductively coupled plasma - optical emission spectrometry (ICP-OES) analysis of bio-organic fertilizers was performed. In general, concentration of nitrogen was higher in the first three biofertilizers i.e. BGH, RB and PS as compared to DL. Germination and glasshouse experiments were conducted to evaluate the effect of four different BIOs on maize growth. The results showed that agro-industrial wastes inoculated with PGPR (BIOs) significantly enhanced (ϸ 0.05) germination percentage (100%) as compared to control (80%), whereas germination index, promptness index and seedling vigour index showed 32%, 34% and 21% increase respectively as compared to control. In the pot experiment, chlorophyll content increased by 28%, relative water content by 39.28%, protein by 3% and amino acid increased by 20.73% as compared to control. It was concluded that there is a positive effect of BIOs on germination parameters and the growth of maize. Thus, these BIOs can be recommended to farmers for the production of maize. Graphical abstract: Image 1 Highlights: Isolated Burkholderia cenocepacia showed plant growth promotion characters. Solid state fermentation of different agroindustrial wastes with Burkholderia cenocepacia produced biofertilizers (BIOs). BIOs inoculation enhanced growth and other parameters of maize.